(untitled) (Annals of Medical Research, 2024)
Aim: Intracranial arachnoid cysts develop from the arachnoid membrane between the membranes called pia mater and dura mater, located on the brain and cerebellum. The aim of this retrospective study is to reveal our clinic’s approach to intracranial arachnoidal cysts, which can be seen incidentally in all age groups, in the light of current literature. Materials and Methods: In our study, we retrospectively analyzed the clinical and radiological findings of a total of 136 patients diagnosed with intracranial arachnoid cysts in both genders and all age groups between January 1, 2017 and December 31, 2023. The localization of the arachnoid cyst was examined in the electronic medical records of the patients who had brain tomography and magnetic resonance imaging during the said interval. The gender, age groups, symptoms, treatment approaches and prognoses of the patients were analyzed. Results: The number of patients diagnosed with arachnoid cyst in our radiological examinations was 136. The prevalence was higher in men than in women; 94 patients were male (69.1%) and 42 patients were female (30.1%). 72 patients were 20 years of age or younger (52.9%). Among 136 patients, only 11 patients were found to have more than one arachnoid cyst in terms of localization (8.1%). In terms of localization, the most common locations were the middle fossa, 52 patients (38.2%). Retrocerebellar location was in 43 patients (31.6%), convex location was in 9 patients (6.6%), and anterior fossa location was in 32 patients (23.5%). Only 42 (30.9%) of 136 patients with radiologically detected arachnoid cysts had clinically significant symptoms. Other patients were detected incidentally during neuroradiological examinations performed for trauma or other reasons. During follow-up, an increase in the size of the cyst was observed in only 9 patients (6.6%). The number of patients operated on in our clinic was only 7 (5.1%). During the follow-up period of the remaining patients, only 3 patients had clinical improvement in their symptoms (2.2%). Conclusion: Arachnoid cysts are frequently encountered incidentally in radiological intracranial imaging today, and their incidence increases in the first 20 years of life. While very few patients show clinically significant neurological symptoms, asymptomatic patients do not require surgical treatment. It is recommended that asymptomatic patients be protected from head trauma and periodic neurosurgery outpatient clinic follow-up.